Late Osseointegration Failure of Implant Case - Kirk, Pia C.; Chandran, Ravi; Lott, James (Journal of Case Reports in Dental Medicine, 2021)
Objective: Dental implants success is indicated by ability to osseointegrate to bone. Failures can be delayed.Methods: Patient received an implant in anterior maxilla. Results:  Implant #10 appeared to initially osseointegrate.  Signs of failure began 3 weeks after restorative impression.Conclusion: Medication interference with osseointegration or failure due to occlusion.